2020
DOI: 10.3390/cancers12102809
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Chromosomal Instability of PTEN-Deficient Triple-Negative Breast Cancer Cell Lines for the Sensitization Against PARP1 Inhibition in a Replication-Dependent Manner

Abstract: Chromosomal instability (CIN) is an emerging hallmark of cancer and its role in therapeutic responses has been increasingly attracting the attention of the research community. To target the vulnerability of tumors with high CIN, it is important to identify the genes and mechanisms involved in the maintenance of CIN. In our work, we recognize the tumor suppressor gene Phosphatase and Tensin homolog (PTEN) as a potential gene causing CIN in triple-negative breast cancer (TNBC) and show that TNBC with low express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…To test the hypothesis that therapy resistance manifests during S-phase, DNA replication processes in the two most resistant and most sensitive cell lines were studied in detail [ 19 , 20 , 21 , 22 ]. The focus was on both the protection of the already replicated DNA strand (fork protection) and the restart of replication after damage repair (fork recovery) ( Figure 4 A,B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To test the hypothesis that therapy resistance manifests during S-phase, DNA replication processes in the two most resistant and most sensitive cell lines were studied in detail [ 19 , 20 , 21 , 22 ]. The focus was on both the protection of the already replicated DNA strand (fork protection) and the restart of replication after damage repair (fork recovery) ( Figure 4 A,B).…”
Section: Resultsmentioning
confidence: 99%
“…Replication is mainly controlled by activation of the kinase CHK1 through phosphorylation [ 19 , 20 , 21 ]. To study CHK1 activation specifically in S phase, UV irradiation was used [ 22 ] ( Figure 4 F).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The PARP1 inhibitors, iniparib and olaparib, are effective for the treatment of triple negative breast cancer (TNBC) and BRCA‐associated BC, which take up ∼40% of the currently diagnosed BC [12]. It is demonstrated that PARP1 inhibitors could treat BC through the crosstalk between NF‐κB, ERK, JNK, or other signaling pathways and PARP1 [13,14]. Many of the pathways are similar to YHD for the treatment of BC.…”
Section: Introductionmentioning
confidence: 99%
“…However, outcomes are less favorable for those patients with residual disease [ 9 ]. Emerging data demonstrate that TNBCs harbor increased levels of unstable aneuploidy, mitotic errors, and chromosomal instability (CIN), and together these are responsible for the heterogeneity and therapeutic resistance observed in this disease [ 10 12 ]. While low/moderate level CIN promotes cancer cell fitness, allowing cells to adapt and survive chromosomal insults and environmental stress, the excessive rates of CIN induced by taxanes causes excessive, unrecoverable damage [ 12 ].…”
mentioning
confidence: 99%